TINJAUAN MAZHAB SYAFI’I TERHADAP PULANGNYA SUAMI KARENA NUSYUZNYA ISTRI : (Studi Kasus Di Desa Sumber Waru, Kec. Waru, Kab. Pamekasan) - Humaidi Humaidi; Mohsi Mohsi; Kamali Kamali (Qisth : Jurnal Studi dan Penelitian Hukum Islam, 2024)
Understanding of the wife's nusyuz which caused Sumi to return home in Sumber Waru village, in 2013 there was a case of nusyuz against a husband and wife couple who had only been married for approximately five months, where the wife's nusyuz was caused by her not wanting to move to the residence that her husband had just made. , so that the wife disobeys her husband's orders and does not carry out her obligations, but the husband remains patient in dealing with his wife's behavior and attitude and it is felt that the wife will not stay in her nusyuz for long. This research uses a qualitative study with a descriptive analytical method. The results of research on the form of wife's nusyus that causes the husband to return home in Sumber Waru village, sub-district. Waru, district. Pamekasan is: A wife's neglect and a wife's indifference to her husband's orders, after several months of moving to a new house made by her husband, but the wife returns from her husband's house for no apparent reason and doesn't even return even though she has been persuaded. Imam Syafi'i's opinion regarding the husband's return home due to his wife's nusyus in Sumber Waru village, sub-district. Waru, district. The husband's return home because of his wife's nusyus based on the case above, according to Imam Syafi'i's opinion, is not haram because the hijr arises not from the husband but from the wife, this is because the wife returns home and no one accompanies her husband in his new home. Basically, the husband does not want to hijr, this is proven by the fact that the husband has persuaded the wife to return to her house, but the wife is still adamant about not returning. Because of this, the husband stayed at home alone and did not bring any changes to his household.